The lake club : a novel - Patton, Lina (William Morrow, an imprint of HarperCollins Publishers, 2026)
"A sizzling, soapy summer debut, in which two women in a wealthy lakeside suburb clash over a cute male nanny, pulling the town's darker secrets to the surface"-- Provided by publisher.